Penyelesaian Tindak Pidana Kecelakaan Lalu Lintas Yang Menyebabkan Kematian Melalui Hukum Adat di Kecamatan Pujud - Firman, Fantias; ', Firdaus; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Contractor Traffic and road transport have a strategic role in supporting nationaldevelopment and integration as part of efforts to promote public welfare as mandated by the 1945Constitution of the State of the Re public of Indonesia. Road transport is organized in order torealize the traffic and road transport safely, safe, fast, smooth, orderly, and regularly comfortableand efficient, able to integrate other means of transportation, reach all corners of the land area, tosupport equity, driving and supporting national development at a cost affordable to the purchasingpower.Judging from the development of human life, the occurrence of the law starting from thehuman person who is given by God the mind and behaviors that are continuously carried out byindividuals lead to personal habits, if personal habits are imitated by others, then he will alsobecome the habit of that person. Then if all members of the community practice this then graduallythe habit becomes the custom of the community, so adat is the custom of the community, andcommunity groups gradually make the adat as custom which should apply to all members of thecommunity with sanctions, so become customary law. Customary law is what is accepted and mustbe carried out in the community concerned. In order to maintain the implementation of customarylaw so that there are no irregularities or violations, then among the members of the communitythere is a duty to watch over. Thus, gradually these officers became customary heads.One of the areas in Riau Province that still adheres to customary law is the Pujud area ofRokan Hilir Regency, previously Pujud is a village that has the nickname Kampung Melayu Pujud.In 2011 there has been a criminal act involving traffic accidents causing deaths occurring withinindigenous communities in Kecamatan Pujud that can be resolved through customary law throughconsensus negotiations of indigenous peoples, and customary elements and both parties concernedwith criminal acts the. Traffic Accidents are unexpected and accidental incidental streets involvingvehicles with or without other road users resulting in human casualties and / or human losses.In this case there are differences between national law and customary law, this case thefamilies of the suspect and the victim reported to the local Ninik Mamak so that this serious mistakewas quickly resolved and did not become a grudge between the two parties concerned and broughtto the ground of positive law. The culprit is Mr. Ucok and the victim who died was Tina, the causeof which was the negligence of the victim himself, if the victim rode a motorcycle by speeding andpassing his motorcycle to nudge the car until he had an accident and the victim died.Keywords: criminal – Traffic Accident – Dead